Psychiatric Nurses Providing Post-Stroke Depression Education to Care Partners of Stroke: A Pilot Study - Patricia Zulim; Anjali Perera; Sonja Stutzman; Daiwai Olson (San Beda University, 2019)
Background: Stroke survivors are a higher risk for post-stroke depression (PSD) after they return home from the hospital. Given that many stroke patients have friends or family members (care partners) present after hospital discharge, this pilot study examined the utility of psychiatric nurses educating family members on how to recognize PSD. Methods: This pilot study identified stroke patients and their care partner while they were in the hospital, to provide education on depressive symptoms, community resources, safety resources (e.g., suicide hotline), how to address symptoms of depression with their care partner. A descriptive observational design was used wherein a psychiatric delivered PSD education to the patient's care partner (instead of the patient). Knowledge of depression was assessed immediately prior to-, immediately after-, and at a 2-week follow-up after-, the education intervention. Results: This pilot study was not powered to detect a statistically significant difference. However, among the 20 subjects (mean age 61 years), fewer scores fell in the lower range (less knowledge of depression) immediately after the education and at the 2-week follow-up phone call. Conclusion: This study demonstrates the potential of multi-disciplinary nursing consultation to improve outcomes.